(untitled) (Вестник КазНУ. Серия Востоковедения, 2017)
In this articlewas considered the history of appearance of Turkic Mamelukes in the Middle East and in particular in the Abbasid caliphate. Many researchers think that the first appearance of Turkic Mamelukes was in the IX century and is connected with political events in the Abbasid caliphate. By the end of the power of the Abbasid caliphate Turkic Mamelukes began to appear in lands of the Middle East. They turned into the main military force of Egypt and Syria, and had direct influence on political life of the countries of this territory. Over time Mamelukes turned into the main military and political force of this region.